Distribution and Contribution of Ethnic Groups on Fertility in Indonesia: Population Census Long Form and National Socio-economy Survey - Ekoriano, Mario; Pitoyo, Agus Joko; ., Nawawi; Prasetyo, Yanu Endar (Journal of Ecohumanism, 2025)
Most Indonesian ethnicities have different perspectives in preferring how many children in their family have and what kind of gender must be a priority in their family. This study aimed to analyze the distribution of the ethnic groups and the effect of ethnicity on fertility in Indonesia. This study used the 15 largest ethnic groups in Indonesia using samples of the 2020 Population Census Long Form microdata (N=275,773,774) and married women number 45,153,267. The results of the analysis of ethnic distribution mapping in several regions show that the diversity of the ethnic groups spread to all regions in Indonesia such as the ethnicity of Minangkabau, Bugis, Malay, Chinese, Batak, and Dayak. It was found that the Sasak ethnic group had the highest influence on the birth of many children, which was 8.89 times higher than other ethnic groups in married women even after controlling for other factors. In the simple model, it was also found that the Sasak ethnic group was also the most influential in determining the birth of many children. The Indonesian government implemented policies that may utilize a cultural approach to organize population diversity and distribution, and use performance indicators using the local socio-cultural norms approach.